Arduino-Based Fire Alarm System with GSM Module (International Journal of Innovative Research in Computer Science & Technology, 2022)
This paper outlines the creation of a house  fire alarm using the Global System for Mobile Communications (GSM) Module with the Arduino  system. The primary objective is to avoid fire in order to  ensure safety at home Residents and buildings within the  home also suffered mishaps. Arduino is used Uno board  along with the chip ATmega328. The most important  controller utilised is the Temperature sensor ATmega328  that regulates the house fire warning. LM35 Limited To  detect fire heat, the temperature sensor is utilised. The user  will receive an alert message SMS through GSM module  Short Message Service When the system is detected at or  above 400 C, an alarm notice will be shown on the LCD  display and concurrently an SMS alert will be sent to  people at the high temperature in the house. Test results  will be documented and discussed. It can assist users  enhance safety standards by immediately reacting to  accident prevention using this method. In the case of a  calamity, this will enable the users to protect life and  property.
Keywords: Arduino Uno; Alarm System; Fire Sensor; Global System for Mobile Communications (GSM)